News Production Strategies for Improving Content Quality at iNews Cirebon.id - Rohidin; Khaerudin Imawan (CV. Syntax Corporation Indonesia, 2026)
This research explored the news production strategies employed by the local news media organization, iNews Cirebon.id, in addressing the dilemma between the demand for rapid news publication and the need to ensure credible news content through a rigorous news production process. This research aimed to analyze the news production strategies implemented by iNews Cirebon.id to improve content quality, particularly in responding to the challenges of rapid publication demands, limited resources, and the threat of disinformation in the digital era. The authors conducted an exploratory case study using a descriptive qualitative approach, employing in-depth interviews with participants, namely journalists from iNews Cirebon.id, regarding their news production process from the pre-production to the post-production stages. Based on the findings, this paper argues that several strategic approaches are employed to produce high-quality news content while addressing the challenges of covering breaking news in the digital era. These strategies include prioritizing news issues based on their local impact and verifying information through credible sources using a multilayered verification system, which serves as a crucial mechanism for ensuring factual reporting in time-constrained environments. Furthermore, this research contributes to enriching the field of local journalism studies by demonstrating how well-planned news production strategies, supported by a robust verification mechanism, can sustain news content quality amid the challenges posed by the widespread dissemination of disinformation in today's local media environment.